Small company issues : A case study of Ah Yee Welding - Chan Yee Mong (2015)
This case study studied about the problem faced by a small company, Ah Yee Welding Company. the rpoblems that Ah Yee Welding is encountering are quite similar with other small company.In general, Ah Yee Welding Company is having problem in systematic management and competition with other companies. The company is also having some personnel problem such as lack of skilled workers, the worker's slack behavior, high resignation rate among the workers, and uncomfortable working environment.